Early short-term effects on catecholamine levels and pituitary function in patients with pheochromocytoma or paraganglioma treated with [177Lu]Lu-DOTA-TATE therapy - Gubbi, Sriram; Al-Jundi, Mohammad; Auh, Sungyoung; Jha, Abhishek; Zou, Joy; Shamis, Inna; Meuter, Leah; Knue, Marianne; Turkbey, Baris; Lindenberg, Liza; Mena, Esther; Carrasquillo, Jorge A.; et al. (Frontiers in Endocrinology, 2023)
Purpose: While there are reports of treatment-related endocrine disruptions and catecholamine surges in pheochromocytoma/paraganglioma (PPGL) patients treated with [ 177 Lu]Lu-DOTA-TATE therapy, the spectrum of these abnormalities in the immediate post-treatment period (within 48 hours) has not been previously evaluated and is likely underestimated.The study population included patients (≥18 years) enrolled in a phase 2 trial for treatment of somatostatin receptor (SSTR)-2+ inoperable/metastatic pheochromocytoma/paraganglioma with [ 177 Lu]Lu-DOTA-TATE (7.4 GBq per cycle for 1 -4 cycles). Hormonal measurements [adrenocorticotropic hormone (ACTH), cortisol, thyroid stimulating hormone (TSH), free thyroxine (FT4), follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone, estradiol, growth hormone, prolactin], catecholamines, and metanephrines were obtained on days-1, 2, 3, 30, and 60 per cycle as per trial protocol, and were retrospectively analyzed.Results: Among the 27 patients (age: 54±12.7 years, 48.1% females) who underwent hormonal evaluation, hypoprolactinemia (14.1%), elevated FSH (13.1%), and elevated LH (12.5%) were the most frequent hormonal abnormalities across all 4 cycles combined. On longitudinal follow-up, significant reductions were noted in i. ACTH without corresponding changes in cortisol, ii. TSH, and FT4, and iii. prolactin at or before day-30 of [ 177 Lu]Lu-DOTA-TATE. No significant changes were observed in the gonadotropic axis and GH levels. Levels of all hormones on day-60 were not significantly different from day-1 values, suggesting the transient nature of these changes. However, two patients developed clinical, persistent endocrinopathies (primary hypothyroidism: n=1 male; early menopause: n=1 female). Compared to day-1, a significant % increase in norepinephrine, dopamine, and normetanephrine levels were noted at 24 hours following [ 177 Lu]Lu-DOTA-TATE dose and peaked within 48 hours.Conclusions: [ 177 Lu]Lu-DOTA-TATE therapy is associated with alterations in endocrine function likely from radiation exposure to SSTR2+ endocrine tissues. However, these changes may sometimes manifest as clinically significant endocrinopathies. It is therefore important to periodically assess endocrine function during [ 177 Lu]Lu-DOTA-TATE therapy, especially among symptomatic patients.